Analisa Push dan Pull factor Masyarakat Surabaya Dalam Memilih China Sebagai Destinasi Wisata Keluarga - Karina Emanuela (Tourism Retailing+, 2013)
This descriptive study tries to analyze the most dominant push and pull factor for Surabaya citizen in choosing China as family recreation destination. The samples are 20-60 years old Surabaya citizens who have already gone or will surely be going to China for their family vacation. The instrument used was questionnaires and the data processed using factor analysis method. Based on the result of factor analysis, it is found that the most dominant push factors Prestige, so they can share what they have seen, and experienced in China to other friends or relatives in order to increase social status. While the most dominant pull factors is Exotic and Adaptable Atmosphere, seeking for different atmosphere but still adaptable for entire family.